Thermal management system modelling and component sizing for heavy duty series hybrid electric vehicles. (1st January 2011) - Park, Sungjin; Malikopoulos, Andreas A.; Kokkolaras, Michael; Jung, Dohoy
A thermodynamics-based Vehicle Thermal Management System (VTMS) model for a heavy-duty, off-road vehicle with a series hybrid electric powertrain is developed for analysing thermal behaviour and investigating power consumption under different vehicle driving conditions. The developed model is first used to define an acceptable and reasonable VTMS configuration; design space exploration techniques are then applied to determine optimal component sizes subject to performance and geometry constraints.